Levant trade review and Turkish-American commercial relations (1911-1931) - Küçük, Hasan (My University, 2019)
In this master thesis, the function, content and views of Levant Trade Review, published by the American Chamber of Commerce for the Levant from 1911 to 1931 in Istanbul are studied in relation to the milestones of its time. American Chamber of Commerce for the Levant (ACCL) was established in Istanbul in 1911 when the Chester Project which marked a remarkable attempt of the American capital to take part in the Near East was on the agenda of the Ottoman Chamber of Deputies. ACCL established branches in Selanik, Patras, Izmir, Beyrut, Atina, Kahire and even in the USA. The Chamber was in the intention of gathering the business people who were engaged in trade with the United States of America under an organization to build better conditions for the American interests as well as supporting the Chester Project. However, ACCL was lack of a platform to promote the USA and the Levant as well as a medium of communication. Thus, Levant Trade Review emerged as the resolution to the need for a platform to create a link among members, to promote American products and industry, to introduce regional commodities, trade and investment opportunities in addition to its being a positive source of information about Turkey. During its publication period, Levant Trade Review adopted a non-political stance and preferred to be out of the political and diplomatic conflicts of the region as long as they were irrelevant to the trade and business which were crucial to the American interests. The reports, op-eds and articles of the magazine were prepared by the experts, American consular officers and the employees of the America institutions in the region, which enabled the magazine to follow the up-to-date local conditions and opportunities for the benefit of the Chamber’s members and American entrepreneurs. In this context, this master thesis aims to study Levant Trade Review to constitute a frame for the American views about the changes in the region during the publication period of the magazine. Furthermore, the content of Levant Trade Review was investigated and analyzed to describe the structure and activities of ACCL; to reveal the activities of American companies in the region and to determine the true importance of the commercial ties between two communities through focusing on specific cases of wheat, flour, fruits, nuts and motor vehicles. Furthermore, the repercussions of the Tripoli and Balkan Wars, the World War I and the Turkish Independence War in case of the trade and economy and the developments in the new republic in Turkey and the reforms were all analyzed and studied. Besides, the magazine provided detailed information about the American companies and business organizations works in the region, expectations and views on the economic future of the region as well as the bilateral relations between two countries. Levant Trade Review was in close cooperation with the American institutions and companies as the most widespread business organization in the region and the United States of America. Because of its publication which concentrated on the economic and commercial relations, Levant Trade Review, proffered substantial data on the bilateral commercial relations between the countries in the region and the USA, American companies’ activities in the region while presenting valuable information on the point of view of the Americans on the transformation in the region. Therefore, the magazine is a true resource of information about the American capital in the region and American institutions, operating in health, education and charity.

Bu çalışmada, American Levant Ticaret Odası (Memalik-i Şarkiyye Ticaret Odası) tarafından 1911-1931 yılları arasında İstanbul’da basılan Levant Trade Review isimli iş dünyası dergisinin işlev, içerik ve görüşleri dönemin önemli olayları ile ilişkili olarak incelenmektedir. Amerikan Levant Ticaret Odası, Amerikan sermayesinin Yakın Doğu pazarında yer almak için geliştirdiği meşhur Chester Projesi’nin Osmanlı Mebusan Meclisi’nde görüşülmekte olduğu bir dönemde İstanbul’da 1911 yılında kuruldu ve Selanik, Patras, İzmir, Beyrut, Atina, Kahire ve hatta ABD’de şubeler kurmuştur. Oda, Chester Projesini destekleme planının yanı sıra Amerika Birleşik Devletleri ile ticari ilişkileri olan iş insanlarını, Amerikan çıkarları için daha iyi koşullar inşa etmek üzere bir kurum altında toplamayı da hedeflemiştir. Levant Trade Review da Oda’nın üyeleri arasında bir bağlantı oluşturma, Amerikan ürün ve sanayisinin bölgedeki varlığını artırma, bölgenin ürün, ticaret ve yatırım imkanlarının ABD’de tanıtımını yapma ihtiyacına bir cevap olarak ortaya çıkmıştır. Levant Trade Review basıldığı süre boyunca, politika dışı yayın politikası takip etmiş, Amerikan çıkarları için hayati önem taşımadıkça ticari ve iş alanı dışında yer alan siyasal ve diplomatik çatışmaların dışında kalmayı tercih etmiştir. Uzmanlar, Amerikan konsolosluk görevlileri ve bölgedeki Amerikan kurumları çalışanları tarafından ekonomi üzerine yoğunlaşılarak hazırlanan rapor, görüş ve makaleler derginin ana temasını oluşturmaktadır. Levant Trade Review, bu sayede, Oda üyeleri ve Amerikan girişimcileri yararına güncel yerel koşul ve fırsatları takip etmiş ve bölgenin gelecek vaat eden sektör ve fırsatları hakkında detaylı bilgi sunmuştur. Levant Trade Review, ayrıca, savaşlar, devrimler ve dönüşümler yaşayan bölgenin yerel durum ve gelişmelerinin iş ve ticaret üzerindeki etkilerini, Oda üyeleri ve Amerikan okuyucularına aktarmıştır. Trablusgarb Savaşı, Balkan Savaşları, I. Dünya Savaşı ve Kurtuluş Savaşı’nın ticaret ve ekonomik alandaki etkisini, yeni Türkiye Cumhuriyeti'nin reformlarının yansımalarını analiz ederek, ilgililere ulaştırmıştır. Keza, Amerikan firmalarının ve iş dünyası kurumlarının bölgedeki faaliyetleri ve çalışmaları, bölge ve ülkenin ekonomik geleceği hakkındaki görüşleri ve ABD ile bölge ülkelerinin karşılıklı ticareti hakkında detaylı bilgiler sağlamıştır. Levant Trade Review yukarıda bahsedildiği üzere bölgedeki en yaygın iş dünyası örgütünün yayın organı olması dolayısıyla Amerikan kurum ve şirketleri ile yakın bir işbirliği içerisindedir. Ekonomik ve ticari ilişkiler üzerine yoğunlaşan yayınları sayesinde bölge ülkeleri ve Amerika Birleşik Devletleri arasındaki ticarete ve Amerikan şirketlerinin bölgedeki faaliyetlerine ve yaşanan değişime bakış açılarına ilişkin önemli bilgiler sağlamaktadır. Ayrıca, ABD’de Türkiye hakkında yaptığı çalışmalar ve yayınlar ile de ikili ilişkilerin gelişmesine katkılar sunacaktır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: American Chamber of Commerce for the Levant; American investment; Istanbul; Balkans; Amerikan Levant Ticaret Odası; Amerikan yatırımları